Properties of Raw Saudi Arabian Grey Kaolin Studied by Pyrrole Adsorption and Catalytic Conversion of Methylbutynol - Murad Alsawalha; Elaref Ratemi (Journal of Chemistry)
This current article demonstrates how X-ray fluorescence spectroscopy (XRF) was employed to reveal the major constituents of a sample of natural grey Saudi kaolin. The XRF results showed that it contained 52.90 wt.% silica together with 14.84 wt.% alumina. Additionally, this paper presents a study on the effect of holding times (i.e., 6, 12, 18, and 24 h) using pyrrole adsorption and methylbutynol test reaction (MBOH) on the Saudi grey kaolin (raw material). Temperature-programmed desorption of pyrrole (pyrrole-TPD) results indicated that increases in thermal conductivity detector (TCD) signals are directly proportional to increases in the heat activation holding time. Notably, a raw Saudi grey kaolin sample heated at a holding time of twenty-four hours resulted in the most intense TCD signal. Further, the MBOH transformations produced 3-methyl-3-buten-1-yne (MBYNE), as the main product, indicating the dehydration of MBOH due to the acidic sites of Saudi grey kaolin. The basic catalysis route was operative at the beginning of the reaction as acetone was observed only during the initial thirty-five minutes of the reaction then later dispersed entirely. Its disappearance is attributed to the high silica content of the test sample.